2018
DOI: 10.1002/ajcp.12240
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Networks and Community Attachment and Support Among Recently Resettled Refugees

Abstract: Interventions aimed at enhancing mental health are increasingly centered around promoting community attachment and support. However, few have examined and tested the specific ecological factors that give rise to these key community processes. Drawing from insights from the ecological network perspective, we tested whether spatial and social overlap in routine activity settings (e.g., work, school, childcare) with fellow ethnic community members is associated with individuals' attachment to their ethnic communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 51 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…Moving beyond the use of individual attributes and neighborhood composition as explanations for levels of interaction and cohesion, the present study also contributes to the burgeoning literature on the significance of neighborhood places for residents and communities, situated in the broader ecological perspective (Browning et al 2017a;Browning et al 2017b;Soller et al 2018;Corocan et al 2017;Silver and Clark 2016). Such a perspective also informs larger debates on the role of place and locality in modern society in the context of globalization.…”
Section: Third Places Neighbor Interaction and Cohesion In The Neigmentioning
confidence: 75%
“…Moving beyond the use of individual attributes and neighborhood composition as explanations for levels of interaction and cohesion, the present study also contributes to the burgeoning literature on the significance of neighborhood places for residents and communities, situated in the broader ecological perspective (Browning et al 2017a;Browning et al 2017b;Soller et al 2018;Corocan et al 2017;Silver and Clark 2016). Such a perspective also informs larger debates on the role of place and locality in modern society in the context of globalization.…”
Section: Third Places Neighbor Interaction and Cohesion In The Neigmentioning
confidence: 75%
“…Soller at al. (2018) interviewed 178 recently resettled refugees in a large southwestern city to understand their community attachment and social networks.…”
Section: Institution-driven Brokeragementioning
confidence: 99%
“…However, many low-income people do not have such a network (Campbell, Marsden, and Hurlbert 1986). In fact, survey-based studies have found that poorer people living in high-poverty neighborhoods have smaller nonkin networks and are more likely to be isolated than those living in low-poverty areas (see Small 2007; van Eijk 2010; Burdick-Will 2018; Soller et al 2018; see also Offer 2012). How, then, do low-income people form networks of support?…”
mentioning
confidence: 99%
“…Expanding our notions of social networks could be valuable, as well. Research has shown that accessing shared spaces is related to increased community attachment among recently resettled refugees (Soller et al 2018). Further exploring how shared activity spaces or eco-networks influence resettlement and well-being over time could be a valuable step forward in this research.…”
Section: Discussionmentioning
confidence: 96%